PRAKIRAAN DAERAH POTENSI RAWAN BANJIR DENGAN MENGGUNAKAN LOGIKA FUZZY TSUKAMOTO BERBASIS WEBSITE (STUDI KASUS KOTA PONTIANAK) - , Dwi Marisa Midyanti, Alexsandrana , Sampe Hotlan Sitorus (Coding Jurnal Komputer dan Aplikasi, 2019)
Disaster is an event that disrupts people's lives caused by natural factors and non-natural factors which creates a risk in a region that can be in the form of death, life threatening, and disruption of community activities. Disasters that cause many losses are floods. The main factor of flooding is the high intensity of the rain and the geographical conditions that the river flows through. In this research an application for forecasting potential flood-prone areas will be made using the fuzzy Tsukamoto method which is useful for providing information on areas that have the potential to flood the people of Pontianak City. In fuzzy Tsukamoto method, fuzzy inference system accepts crisp input in the form of firm values, where firm values will be converted into fuzzy sets through fuzzification, inference and defuzzification processes. The end result of these processes will produce output in the form of fuzzy values as system output. This research uses realtime rainfall and river depth data taken from the Pontianak BMKG Maritime website as an input to the application. The value of rainfall used is between 0 - 50 mm, the value of the height of river water used is between 0.5 - 2.5 m, and the value of land height between 0.5 - 1.7 m. From 40 test data, 37 validated data were correctly obtained, thus the accuracy of this study was 92.5%.Â Keywords: Fuzzy Tsukamoto, forecast of flood areas, Pontianak city